Genome survey and genetic characterization of Acacia pachyceras O. Schwartz - Habibi, Nazima; Al Salameen, Fadila; Vyas, Nishant; Rahman, Muhammad; Kumar, Vinod; Shajan, Anisha; Zakir, Farhana; Razzack, Nasreem Abdul; Al Doaij, Bashayer (Frontiers in Plant Science, 2023)
Acacia pachyceras Schwartz. (Leguminoseae), a woody tree growing in Kuwait is critically endangered. High throughput genomic research is immediately needed to formulate effective conservation strategies for its rehabilitation. We therefore, performed a genome survey analysis of the species. Whole genome sequencing generated ~97 Gb of raw reads (92x coverage) with a per base quality score above Q30. The k-mer analysis (17 mer) revealed its genome to be 720Mb in size with an average guanine-cytosine (GC) ratio of 35%. The assembled genome was analyzed for repeat regions (45.4%-interspersed repeats; 9%-retroelements; 2%-DNA transposons). BUSCO assessment of completeness of genome identified 93% of assembly to be complete. Gene alignments in BRAKER2 yielded 34,374 transcripts corresponding to 33,650 genes. Average length of coding sequences and protein sequences were recorded as 1027nts and 342aa, respectively. GMATA software filtered a total of 901,755 simple sequence repeats (SSRs) regions against which 11,181 unique primers were designed. A subset of 105SSR primers were PCR validated and demonstrated for its application in genetic diversity analysis of Acacia. The SSR primers successfully amplified A. gerardii seedlings depicting cross transferability among species. The principal coordinate analysis and the split decomposition tree (bootstrapping runs of 1000 replicates) distributed the Acacia genotypes into two clusters. The flow cytometry analysis revealed the A. pachyceras genome to be polyploid (6x). The DNA content was predicted as 2.46 pg, 1.23 pg, and 0.41 pg corresponding to 2C DNA, 1C DNA and 1Cx DNA respectively. The results provide a base for further high throughput genomic studies and molecular breeding for its conservation.